International law and communicable diseases - Aginam Obijiofor (Bulletin of the World Health Organization, 2002)
Historically, international law has played a key role in global communicable disease surveillance. Throughout the nineteenth century, international law played a dominant role in harmonizing the inconsistent national quarantine regulations of European nation-states; facilitating the exchange of epidemiological information on infectious diseases; establishing international health organizations; and standardization of surveillance. Today, communicable diseases have continued to re-shape the boundaries of global health governance through legally binding and "soft-law" regimes negotiated and adopted within the mandate of multilateral institutions - the World Health Organization, the World Trade Organization, the Food and Agriculture Organization, and the Office International des Epizooties. The globalization of public health has employed international law as an indispensable tool in global health governance aimed at diminishing human vulnerability to the mortality and morbidity burdens of communicable diseases.